Therapeutic Targets for Treatment of Heart Failure: Focus on GRKs and β-Arrestins Affecting βAR Signaling - Mangmool, Supachoke; Parichatikanond, Warisara; Kurose, Hitoshi (Frontiers in Pharmacology, 2018)
Heart failure (HF) is a heart disease that is classified into two main types: HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). Both types of HF lead to significant risk of mortality and morbidity. Pharmacological treatment with β-adrenergic receptor (βAR) antagonists (also called β-blockers) has been shown to reduce the overall hospitalization and mortality rates and improve the clinical outcomes in HF patients with HFrEF but not HFpEF. Although, the survival rate of patients suffering from HF continues to drop, the management of HF still faces several limitations and discrepancies highlighting the need to develop new treatment strategies. Overstimulation of the sympathetic nervous system is an adaptive neurohormonal response to acute myocardial injury and heart damage, whereas prolonged exposure to catecholamines causes defects in βAR regulation, including a reduction in the amount of βARs and an increase in βAR desensitization due to the upregulation of G protein-coupled receptor kinases (GRKs) in the heart, contributing in turn to the progression of HF. Several studies show that myocardial GRK2 activity and expression are raised in the failing heart. Furthermore, β-arrestins play a pivotal role in βAR desensitization and, interestingly, can mediate their own signal transduction without any G protein-dependent pathway involved. In this review, we provide new insight into the role of GRKs and β-arrestins on how they affect βAR signaling regarding the molecular and cellular pathophysiology of HF. Additionally, we discuss the therapeutic potential of targeting GRKs and β-arrestins for the treatment of HF.